Endoscopy in the management of a rudimentary non-communicating functional horn - Shah, Nitin H.; Joshi, Aditi V.; Mourya, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Mullerian anomalies are developmental malformations of the female reproductive tract, often diagnosed late. They are classified into numerous types like a septate uterus, bicornuate or unicornuate uterus etc. A rudimentary non-communicating functional horn is a rare variant of a unicornuate uterus. It may present with a wide spectrum of symptoms like severe dysmenorrhea, infertility, lump in abdomen or rarely maybe diagnosed with a ruptured ectopic in the horn. The diagnosis of this entity is a difficult and challenging. Authors present a case of a young adolescent diagnosed with this Mullerian anomaly, the role of hysteroscopy in confirmation of diagnosis and the management of the patient by laparoscopy successfully. The patient was completely relieved of her symptoms post-surgery.